Influence of n-3 Fish Oil-Enriched Intravenous Lipid Emulsion on Length of Stay and Mortality in Infants Post Intestinal Surgery - Meta Herdiana Hanindita; Khadijah Rizky Sumitro; Nur Aisiyah Widjaja; Roedi Irawan; Boerhan Hidayat (Health Notions, 2019)
Background: Parenteral nutrition plays an important role in the infants post intestinal surgery. Currently, n-6 soybean oil-based intravenous lipid emulsion (IVLE) is used as a standard. n-6 have been shown increases biomarkers of inflammation while n-3 have shown positively influence clinical outcomes due to their immunomodulatory action. The aim of this study is to investigate the influence of n-3 fish oil-enriched IVLE on mortality and length of stay in infants post intestinal surgery. Methods: A medical record retrospective study was undertaken in infants post intestinal surgery at Dr. Soetomo Hospital in 2016-2017. Infants with intestinal atresia who had PN for at least three days were included. The n-6 soybean oil-based and n-3 fish oil-enriched IVLE were used. Incomplete data was excluded. Results: There were 19 infants (12/19 boys) included in this study. 10/19 infants received the n-6 soybean oil-based IVLE. The duration and dose of IVLE used were 16.52±11.34 days and 1.80±0.44 g/kg/day. Mortality rate was significantly lower in n-3 fish oil-enriched IVLE group (P=0.02) while there was no difference on length of stay (P=0.484).Conclusion: Infants who received the n-3 fish oil-enriched IVLE have a lower mortality rate but there is no difference on length of stay. Keywords: Infants, Intestinal surgery, Intravenous lipid emulsion, Length of stay, Mortality